Greek and Roman Technology : A Sourcebook of Translated Greek and Roman Texts - Sherwood, Andrew N. (Routledge Sourcebooks for the Ancient World Ser, 2019)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of illustrations -- Preface to the second edition -- Extract from the preface and acknowledgements of the first edition -- List of abbreviations -- Introduction -- 1 The rise of humans and human technology -- 2 Sources of energy and basic mechanical devices -- 3 Agriculture -- 4 Food processing -- 5 Mining and quarrying -- 6 Metallurgy -- 7 Sculpture -- 8 Construction engineering -- 9 Hydraulic engineering -- 10 Household crafts, health and well-being, and workshop production -- 11 Transport and trade -- 12 Record-keeping -- 13 Military technology -- 14 Attitudes towards labour, innovation, and technology -- Indexes -- A Index of Passages Translated -- B Subject Index.